Anti-Adhesion Activity of A2-type Proanthocyanidins (a Cranberry Major Component) on Uropathogenic E. coli and P. mirabilis Strains - Daria Nicolosi; Gianna Tempera; Carlo Genovese; Pio M. Furneri (Antibiotics, 2014)
Urinary tract infections (UTIs) are relatively common in women and may be classified as uncomplicated or complicated, depending upon the urinary tract anatomy and physiology. Acute uncomplicated cystitis (AUC) occurs when urinary pathogens from the bowel or vagina colonize the periurethral mucosa and reach the bladder. The vast majority of episodes in healthy women involving the same bacterial strain that caused the initial infection are thought to be reinfections. About 90% of AUC are caused by uropathogenic Escherichia coli (UPEC), but Proteus mirabilis also plays an important role. Several studies support the importance of cranberry (Vaccinium macrocarpon) proanthocyanidins in preventing adhesion of P-fimbriated UPEC to uroepithelial cells. In this study, we evaluated the in vitro anti-adhesion activity of A2-linked proanthocyanidins from cranberry on a UPEC and Proteus mirabilis strains and their possible influence on urease activity of the latter. A significant reduction of UPEC adhesion (up to 75%) on the HT1376 cell line was observed vs. control. For the strains of P. mirabilis there was also a reduction of adhesion (up to 75%) compared to controls, as well as a reduction in motility and urease activity. These results suggest that A2-type cranberry proanthocyanidins could aid in maintaining urinary tract health.